Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Which expression is equivalent to the given expression?

7x−3


7x−3x

3−7x

4x−3+3x

3−6+3x


Sagot :

Answer:

4x–3+3x

Step–by–step explanation:

Look at each term as positive or negative. I will use brackets for the sake of clarity, but that is not necessary. Here, that would look like:

[+4x] [–3] [+3x]

Rearrange the terms.

[+4x] [+3x] [–3]

Remove the brackets.

4x +3x –3

Simplify.

7x – 3

Answer:

  • Option C

Step-by-step explanation:

Let's verify all the options.

Option A:

  • 7x - 3x = 7x - 3
  • => 4x = 7x - 3 (False)

Option B:

  • 3 − 7x = 7x - 3
  • => 3 + 3 = 14x (False)

Option C:

  • 4x − 3 + 3x = 7x - 3
  • => 7x - 3 = 7x - 3 (True)

Option D:

  • 3 − 6 + 3x = 7x - 3
  • => 3x - 3 = 7x - 3
  • => 3x = 7x (False)

We can conclude that option C is correct.

Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.